Teatr Telewizji Łódzkiego Ośrodka Telewizyjnego – widowiska i ich twórcy na przestrzeni lat - Bachura-Wojtasik, Joanna (Acta Universitatis Lodziensis. Folia Litteraria Polonica, 2015)
This article attempts to capture the phenomenon of Lodz Television Theatre and to reveal changes in it over the years, i.e. from the foundation of the ŁOT Television Theatre up to the 1990s, when the production of such performances ended at the Lodz Television Centre.